Mentoring as service-learning: The relationship between perceived peer support and outcomes for college women mentors. (December 2015) - Marshall, Jenna H.; Lawrence, Edith C.; Lee Williams, Joanna; Peugh, James
Highlights: College women youth mentors in a service-learning program were assessed. Mentors' perceived peer support was associated with stronger sense of autonomy. Mentors' perceived peer support was associated with greater ethnocultural empathy. Peers may provide effective support for college students engaged in service-learning. Recommendations are made for enhancing training and support for service-learners. Abstract: This study examined whether peer support was related to psychosocial outcomes for college women serving as youth mentors in the Young Women Leaders Program (YWLP), a service-learning mentoring program. The outcomes assessed were college students' ethnocultural empathy and their sense of competence, relatedness, and autonomy. Data included questionnaires completed by YWLP mentors (YWLP; n = 227) and college women with (CS; n = 230) and without (no CS; n = 105) alternative community service involvement. Results showed that YWLP mentors' level of perceived peer support was associated with stronger outcomes in autonomy as compared to the CS group and in ethnocultural empathy as compared to both comparison groups. These findings extend the literature on effective support for college service-learning participants.